Karakterisasi Pati Kimpul (Xanthosoma sagittifolium) dengan Modifikasi Heat Moisture Treatment - Laksmi Putri Ayuningtyas; Kavadya Syska; Hikmah Yuliasari (Scientific Timeline, 2021)
Heat moisture treatment (HMT) refers to a physical method for altering physicochemical and molecular properties of root and tuber starches. Principally, the starch's moisture content is adjusted to 10-35% and then exposed to heat (90-120°C) above the glass transition and gelatinization temperature for 15 minutes until 16 hours. Low moisture content did not allow starch gelatinization. In this work, cocoyam starch was modified using HM, with the moisture content of 25% and heating temperature of 105°C for 4 hours. Results show that HMT did not disrupt the cocoyam starch granule structure, while it increased swelling power and water binding capacity and decreased oil binding capacity compared to native starch.